Enhanced photoelectrochemical properties of TiO(2) nanorod arrays decorated with CdS nanoparticles - Xie, Zheng (Sci Technol Adv Mater, 2014)
TiO(2) nanorod arrays (TiO(2) NRAs) sensitized with CdS nanoparticles were fabricated via successive ion layer adsorption and reaction (SILAR), and TiO(2) NRAs were obtained by oxidizing Ti NRAs obtained through oblique angle deposition. The TiO(2) NRAs decorated with CdS nanoparticles exhibited excellent photoelectrochemical and photocatalytic properties under visible light, and the one decorated with 20 SILAR cycles CdS nanoparticles shows the best performance. This can be attributed to the enhanced separation of electrons and holes by forming heterojunctions of CdS nanoparticles and TiO(2) NRAs. This provides a promising way to fabricate the material for solar energy conversion and wastewater degradation.